Colour perception deficits after posterior stroke: Not so rare after all?. (February 2023) - Munk, Amalie H.; Starup, Elisabeth B.; Lambon Ralph, Matthew A.; Leff, Alex P.; Starrfelt, Randi; Robotham, Ro J.
Abstract: Cerebral achromatopsia is an acquired colour perception impairment caused by brain injury, and is generally considered to be rare. Both hemispheres are thought to contribute to colour perception, but most published cases have had bilateral or right hemisphere lesions. In contrast to congenital colour blindness that affects the discrimination between specific hues, cerebral achromatopsia is often described as affecting perception across all colours. Most studies of cerebral achromatopsia have been single cases or case series of patients with colour perception deficits. Here, we explore colour perception deficits in an unbiased sample of patients with stroke affecting the posterior cerebral artery ( N  = 63) from the Back of the Brain project. Patients were selected based on lesion location only, and not on the presence of a given symptom. All patients were tested with the Farnsworth D-15 Dichotomous Colour Blindness Test and performance compared to matched controls ( N  = 45) using single case statistics. In patients with abnormal performance, the patterns of colour difficulties were qualitatively analysed. 22% of the patients showed significant problems with colour discrimination (44% of patients with bilateral lesions, 28% with left hemisphere lesions and 5% with right hemisphere lesions). Lesion analyses identified two regions in ventral occipital temporal areas in the left hemisphere as particularly strongly related to impaired performance in colour perception, but also indicated that bilateral lesions are more strongly associated with impaired performance that unilateral lesions. While some patients only had mild deficits, colour perception impairments were in many cases severe. Many patients had selective deficits only affecting the perception of some hues. The results suggest that colour perception difficulties following PCA stroke are common, and that they vary in severity and expression. In addition, the results point towards bilateral processing of colour perception with a left hemispheric domination, contradicting previous reports.